MINOR TOOTH MOVEMENT FOR CROWDING AND ANTERIOR CROSSBITE: A PICTORIAL CASE REPORT - MOHAMMAD KHURSHEED ALAM; ANAS IMRAN; FAZAL SHAHID; SHIFAT A NOWRIN (International Journal of Pharma and Bio Sciences, 2015)
Anterior crossbite can be defined as reverse overlap of incisors. Crowding can be referred to as a discrepancy of tooth size in relation to arch size resulting in malalignment of teeth due to scant space. Crossbite can cause excessive attrition, poor masticatory efficiency, poor gingival health and TMJ problems. This is a case-report of diagnosis and management of 24 year old female with esthetic concerns. Clinical findings indicate a class I malocclusion with anterior crossbite and moderate crowding. Non extraction treatment was planned with fixed orthodontic alignment to produce minimal tooth movement. Interproximal enamel reduction was done to create spaces.